Household risk taking after the financial crisis - Necker, Sarah; Ziegelmeyer, Michael (Quarterly Review of Economics and Finance, 2016)
This study investigates whether and how the crisis in 2008/2009 affects households' risk attitudes, subjective risk and return expectations, and planned financial risk taking using the German SAVE study. Households' wealth change from end-2007 to end-2009 is not found to have an effect. However, households that attribute losses to the crisis decreased their risk tolerance and planned risk taking; the probability of expecting an increase in risks and returns is increased. According to economic theory, wealth changes attributed to a dramatic event should not have a different effect than other wealth changes. The results suggest an emotional reaction.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Emotions; Financial crisis; Risk preferences; Stock market expectations; Wealth fluctuations